Sustainable Tourism Ecosystem In Strategic National Tourism Area (KSPN) Borobudur Yogyakarta and Prambanan (BYP) - Muhamad, Muhamad; Baiquni, Muhammad; Wiryanto, Wiryanto (Faculty of Geography, Universitas Gadjah Mada, 2024)
This research aims to understand the tourism ecosystem as a complex phenomenon. The study attempts to design aspects that can advance the tourism sector, such as linkage, value chain, and interconnectivity systems. To maximize the tourism sector, the support of the BGCM (business, government, community, academic, and media) is needed to run as well as possible. Research conducted in Borobudur Yogyakarta Prambanan (BYP). This research uses the method of explorative descriptive research with a qualitative approach, aimed at studying objects naturally and in depth, where the researcher is the key instrument. The results of this study resulted in a road map of Sustainable Tourism Development relating to the application and issues of sustainable tourism with the optimization of the role of BGCM. BGCM has a role in creating tourism benefits that yield to the community and the environment in the National Strategic Tourism Area.